Pengaruh pemberian hormon tumbuh dan diameter stek terhadap pertumbuhan stek jeruk nipis tanpa biji (citrus aurantifolis s) - ANDI HERAWATI (Perbal : Jurnal Pertanian Berkelanjutan, 2015)
This study aims to determine the effect of growth hormone and diameter cuttings seedless lime (Citrus aurantifolis S). This research conducted experiments using a randomized block design (RAK) are arranged in a factorial of two factors. The first factor is the growth hormone (H) and the second factor is the cutting diameter (D). The results showed that growth of hormone Rootone-F with diameter cuttings 0.7 cm and interactions gives the best effect on the growth of seedless lemon cuttings. Keyword : Growth Hormone, Diameter Cuttings, Seedless Lime